University, Media and Public Opinion (Uruguay, 1956-1973) - Gapenne, Camille (CIAN-Revista de Historia de las Universidades, 2024)
This paper analyzes the evolution of the communication of the Universidad de la República in Uruguay, between the election of Mario Cassinoni as Rector in 1956 and the coup and intervention of the University in 1973. This period is characterized by increasing repression and censorship, the political radicalization of broad sectors of the population and the deepening of the economic crisis the country was going through. The presentation of this process of emergence, diversification and systematization of a communication strategy is a framework that gives us the possibility to discuss several issues such as the dichotomous representation of the confrontation between the prensa grande and the University, the evolution of the conception of the relationship between the University and the “public opinion” or the gradual formation of an “internal front” among the university actors, necessary in order to face the frequent att st the University and its members.